Theme choice in oral case presentations: differences between medical novices and experts - Khan, Munir; Chan, Mei Yuit; Mohamad Ali, Afida; Mohd Isa, Muhammad; Narayanan, Prepageran; Abu bakar, Zulkiflee; Yap, Ngee Thai; Foo, Yoke Loong; Hoo, Fan Kee; Hod, Rafidah (Elsevier, 2021)
The clinical case presentation is an important mode of professional communication as well as an academic genre in medical education. Examining both students’ and experienced doctors’ linguistic practices can reveal how students differ in their underlying knowledge, interpretation and execution of the case presentation that mark their novice status. In this paper, we describe differences in the use of theme in initiating sentences in case presentations produced by doctors and medical students. Theme analysis, an analysis of the linguistic elements that are used to begin a clause, was used. The data comprised 50 audio- recorded oral case presentations elicited from 20 doctors and 30 students in two medical schools. Choice of theme in doctors’ and students’ presentations was compared. The findings show that doctors and students differ significantly in their use of specific theme types indicating their different understanding and use of the oral case presentation as well as their social position in the professional field. Indexing students’ novice status are differences in the use of conjunctive adjuncts, interpersonal, existential and pronoun themes, and marked themes as overt signalling of the presentation structure. These findings contribute to provide some insight on students’ learning trajectory and can inform appropriate educational interventions.